2020
DOI: 10.1111/mcn.12911
|View full text |Cite
|
Sign up to set email alerts
|

Infant and young child feeding practices and child linear growth in Nepal: Regression–decomposition analysis of national survey data, 1996–2016

Abstract: Suboptimal infant and young child feeding (IYCF) practices have profound implications on child survival, health, growth, and development. First, our study analysed trends in 18 IYCF indicators and height-for-age z-score (HAZ) and stunting prevalence across Nepal's Family Health Survey 1996 and four rounds of Nepal Demographic and Health Surveys from 2001-2016. Second, we constructed multivariable regression models and decomposed the contribution of optimal IYCF practices on HAZ and stunting prevalence over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
4
14
3
1
Order By: Relevance
“…Our study found that mothers who produced crops enough for 12 months were more likely to meet the minimum acceptable diet. A similar finding was reported by the further analysis of NDHS study 2016 [ 16 ]. Mothers who had correct knowledge on recommended feeding practices were more likely to meet the minimum acceptable diet [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that mothers who produced crops enough for 12 months were more likely to meet the minimum acceptable diet. A similar finding was reported by the further analysis of NDHS study 2016 [ 16 ]. Mothers who had correct knowledge on recommended feeding practices were more likely to meet the minimum acceptable diet [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…IYCF is a priority strategy of the Ministry of Health and Population. Despite the scale-up of this program was scaled up to all districts of Nepal, IYCF practices remain poor [ 16 ]. Therefore, it is more important to understand local and regional child feeding practices and their associated factors before developing strategies aimed to improve child feeding practices in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier analysis, Caul eld, Bentley (11) also observed a positive association between prolonged breastfeeding and malnutrition among child less than three years old. Our results on breastfeeding duration and HAZ are not in agreement with ndings among Nepalese (18) and Guatemalan ( 16) children, in whom breastfeeding duration was shown to be positively associated with HAZ. The differences in the results could be due to failure to account for confounding in some studies or mediating factors such as age of the children.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, our observed progress on HAZ and stunting prevalence might be attributed to transgenerational improvements in maternal nutrition (Addo et al, 2015 )—captured in our models by enhanced iron supplementation during pregnancy, maternal BMI and height (Hasan, Magalhães, Williams, & Mamun, 2016 ), and reduced maternal reproductive burden (birth order and birth interval)—and improvements in postnatal child care and feeding practices (Na et al, 2018 ), as indicated by the substantial increase in EIBF. Furthermore, advances in the spectrum of age‐appropriate IYCF practices, not covered due to data constraints, have been reported in Nepal over the past two decades (Benedict, Craig, Torlesse, & Stoltzfus, 2018 ; Hanley‐Cook, Argaw, Dahal, Chitekwe, & Kolsteren, 2022 ). These positive child caring trends might be attributed to scaling up nutrition‐specific strategies advocating for optimal IYCF (Cunningham et al, 2017 ; Locks et al, 2018 ) and national policy, such as the National Safe Motherhood Policy (1998), National Policy on Skilled Birth Attendants (2006), and National IYCF Strategy (2014; Karn, Devkota, Uddin, & Thow, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, comparability is essential in regression–decomposition approaches and thus constrained our analysis to use variables that were available across all five survey rounds. To illustrate, in particular for nutrition‐specific factors, comprehensive data on age‐specific IYCF indicators were absent for the NFHS 1996 and early NDHS rounds (Hanley‐Cook et al, 2022 ), which limited their inclusion in our analysis. Moreover, potential limitations of the explanatory variables in our linear regression models should also be recalled, including the fact that household asset indices fail to account for a durable's age and depreciation (Harttgen & Vollmer, 2013 ), improved health care coverage might not necessarily imply high‐quality services (Acharya, Sharma, Dulal, & Aryal, 2018 ), water sources do not specifically capture water quality (Klasen, Lechtenfeld, Meier, & Rieckmann, 2012 ), improved sanitation might be better captured at the community level (Spears, 2013 ), EIBF and bottle‐feeding strictly apply to children aged 0–23 months, and duration of breastfeeding is ideally captured as a median at population level (WHO, 2008 , 2010 ).…”
Section: Discussionmentioning
confidence: 99%